The surface water quality ecotoxicological assessment of Wolin Island - Paweł Czyryca; Mariusz Samołyk (Kazimierz Wielki University, 2017)
Determining the quality of surface waters is very important from human health point of view. Proper recognition of the ecological condition of surface waters allows to take appropriate actions to improve it. This paper presents the results of physico-chemical analyses and toxicological studies of surface waters of Wolin Island. The toxicity of the samples was determined by the acute toxicity test Thamnotoxkit F. based on freshwater crustaceans Thamnocephalus platyurus. The results enabled to assess the ecological state of the examined waters.